2013
DOI: 10.1371/journal.pone.0062070
|View full text |Cite
|
Sign up to set email alerts
|

A Texture Based Pattern Recognition Approach to Distinguish Melanoma from Non-Melanoma Cells in Histopathological Tissue Microarray Sections

Abstract: AimsImmunohistochemistry is a routine practice in clinical cancer diagnostics and also an established technology for tissue-based research regarding biomarker discovery efforts. Tedious manual assessment of immunohistochemically stained tissue needs to be fully automated to take full advantage of the potential for high throughput analyses enabled by tissue microarrays and digital pathology. Such automated tools also need to be reproducible for different experimental conditions and biomarker targets. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 39 publications
(43 reference statements)
0
28
0
Order By: Relevance
“…[2][3][4][5][6][7] This technology can become fundamental in exploring the human proteome considering the information acquired from human genome efforts [17][18][19] since it can provide a means to explore, in a rapid and costeffective manner, the huge number of antibodies being generated from the non-redundant protein database. In addition, both proteomic and genomic data can be simultaneously obtained from the same specimen.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7] This technology can become fundamental in exploring the human proteome considering the information acquired from human genome efforts [17][18][19] since it can provide a means to explore, in a rapid and costeffective manner, the huge number of antibodies being generated from the non-redundant protein database. In addition, both proteomic and genomic data can be simultaneously obtained from the same specimen.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, C-Path has identified that features of the stromal tissue adjacent to the cancer were better predictors of patient survival than the features of tumor cells alone. Similar quantitative algorithms have been developed for the automated quantification of IHC-determined protein expressions in melanocytes (27), for the automated assessment of the extent of malignant nuclei in colon cancer histology images (28), and for quantifying the architectural complexity in breast and prostate cancer specimens (29, 30). Our group also used quantitative segmentation algorithms to automatically determine scores for HER2-positive, ER-positive, and PR-positive cells within digitized histology images of breast cancer tissues (31), to correlate patient ER statuses with spatial distributions of ER-positive and ER-negative cells, as well as tumor vascular density and vascular area (32), and to determine the extent of the drug-mediated cytotoxic and apoptotic effects in osteosarcoma xenotransplants (33).…”
Section: Evaluation Of the Hypothesismentioning
confidence: 99%
“…As a result, C-Path has identified that features of the stromal tissue adjacent to the cancer were better predictors of patient survival than the features of tumor cells alone. Similar quantitative algorithms have been developed for the automated quantification of IHC-determined protein expressions in melanocytes (27), for the automated assessment of the extent of malignant nuclei in colon cancer histology images (28), and for quantifying the architectural complexity in breast and prostate cancer specimens (29,30). Our group also used quantitative segmentation algorithms to automatically determine scores for HER2-positive, ERpositive, and PR-positive cells within digitized histology images of breast cancer tissues (31), to correlate patient ER statuses with spatial distributions of ER-positive and ER-negative cells, as well as tumor vascular density and vascular area (32), and to determine the extent of the drug-mediated cytotoxic and apoptotic effects in osteosarcoma xenotransplants (33).…”
Section: Evaluation Of the Hypothesismentioning
confidence: 99%